Characteristic of Soil Physical Properties Derived from Pyritic-Contained Sediment of Musi Banyuasin as by Affected by Drying Treatment - Kukuh Murtilaksono; Sudarmo .; Susila Herlambang; Sjarif . (Jurnal Ilmu Tanah dan Lingkungan, 2000)
Greenhouse and laboratory research at the Department of Soil Science, Faculty of Agriculture IPB has been conducted about treatment of drying on acid sulphate soil coloum from Musi Banyuasin to examine the effect on soil physical properties. Soil coloum of 95 cm height is maintained submerged, aside from other soil coloums drained at 50 cm and 75 cm depth are drying treatment of 2, 4, 6, and 8 weeks. Drying treatment at 75 cm depth lowering soil surface 0.8 and 2.9 crn at the firstand eighth week of drying, respectively. The soil subsidence is affected by organic matter decomposition and swelling - shrinkage characteristic of 2:1 clay mineral. Drying treatmentsignificantly increasing aggregate stability from 54.69 to 57.19 at 15 cm depth, decreasing it from 57.29 to 51.19 at 45 cm depth at sixth week, and 49.59 to 45.82 at 75 cm depth at fourth week.Although the result has irregular pattern, drying treatment significantly increasing soil bulk density at 15 an depth from 0.83 to 0.95 glcm3, decpasing at 45 cm depth from 0.69 to 0.45 glcm3at sixth week, and increasing from 0.63 to 0.72 g/cm at 75 cm depth at fourth week. The incremental anddecreasing is more caused by organic matter decomposition and soil aggregate sementation by iron resulted from pyrite oxidation. Drying treatment significantly affecting soil porosity, permeability and COLE at several depth, atthough the pattern is irregular.